Conservatism predicts lapses from vegetarian/vegan diets to meat consumption (through lower social justice concerns and social support). (1st January 2018) - Hodson, Gordon; Earle, Megan
Abstract: Lapses from vegetarian and vegan (i.e., veg*n) food choices to meat consumption are very common, suggesting that sustaining veg*nism is challenging. But little is known about why people return to eating animals after initially deciding to avoid meat consumption. Several potential explanatory factors include personal inconvenience, meat cravings, awkwardness in social settings, or health/nutrition concerns. Here we test the degree to which political ideology predicts lapsing to meat consumption. Past research demonstrates that political ideology predicts present levels of meat consumption, whereby those higher in right-wing ideologies eat more animals, even after controlling for their hedonistic liking of meat (e.g., Dhont & Hodson, 2014). To what extent might political ideology predict whether one has lapsed from veg*n foods back to meat consumption? In a largely representative US community sample (N = 1313) of current and former veg*ns, those higher ( vs . lower) in conservatism exhibited significantly greater odds of being a former than current veg*n, even after controlling for age, education, and gender. This ideology-lapsing relation was mediated (i.e., explained) by those higher ( vs . lower) in conservatism: (a) adopting a veg*n diet for reasons less centered in justice concerns (animal rights, environment, feeding the poor); and (b) feeling socially unsupported in their endeavor. In contrast, factors such as differential meat craving or lifestyle inconvenience played little mediational role. These findings demonstrate that ideology and justice concerns are particularly relevant to understanding resilience in maintaining veg*n food choices. Implications for understanding why people eat meat, and how to develop intervention strategies, are discussed.